2019
DOI: 10.3390/ijerph16091649
|View full text |Cite
|
Sign up to set email alerts
|

Management of STEC Gastroenteritis: Is There a Role for Probiotics?

Abstract: Shiga toxin-producing Escherichia Coli (STEC) infections routinely run as a common gastroenteritis, but in many cases they may evolve towards hemolytic uremic syndrome (HUS). HUS is a rare disease characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. Gut microorganisms have a fundamental impact on human physiology, because they modulate normal intestinal functions and play a pivotal role in influencing the local and systemic immune responses. Despite surveillance establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Finally, we use machine-learning methods and sepsis-related intestinal bacteria to construct a classifier for distinguishing sepsis, and the AUC value can reach 81.25%; although further verification is needed, it shows that the composition of gut microbiota has certain potential for diagnosis of sepsis. In addition, Giordano et al found that probiotics may play a promising role in modifying the intestinal microbiota of patients with STEC (Shigatoxin-producing E. coli ) gastroenteritis, thus avoiding the onset or, at least, reducing the severity of Hemolytic Uremic Syndrome ( 36 ). Managing dysbiosis and manipulating the microbial environment with probiotic supplementations is a promising research field for promoting health and preventing diseases also in term and preterm neonates ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we use machine-learning methods and sepsis-related intestinal bacteria to construct a classifier for distinguishing sepsis, and the AUC value can reach 81.25%; although further verification is needed, it shows that the composition of gut microbiota has certain potential for diagnosis of sepsis. In addition, Giordano et al found that probiotics may play a promising role in modifying the intestinal microbiota of patients with STEC (Shigatoxin-producing E. coli ) gastroenteritis, thus avoiding the onset or, at least, reducing the severity of Hemolytic Uremic Syndrome ( 36 ). Managing dysbiosis and manipulating the microbial environment with probiotic supplementations is a promising research field for promoting health and preventing diseases also in term and preterm neonates ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of certain probiotics to humans or reservoir animals may reduce colonization and carriage of STEC, which will prevent and/or reduce the risk of infection and transmission of the pathogenic bacteria (Sargeant et al, 2007;Corr et al, 2009). Protective and beneficial capabilities of probiotics have been described in several studies in which probiotics have been applied prior to an STEC infection of cultured cells or in mice (recently reviewed in detail by (Eaton et al, 2011;Mogna et al, 2012;Chen et al, 2013;Kakisu et al, 2013;Rund et al, 2013;Cordonnier et al, 2017;Giordano et al, 2019)). Significant inhibitory effects against the growth of STEC have been demonstrated for several Lactobacillus…”
Section: Alternative Approaches Using Antimicrobial Agents Probioticsmentioning
confidence: 99%
“…coli Nissle, Enterococcus faecium YF5, Enterococcus faecalis (Symbioflor), Bifidobacterium longum, and others. Moreover, use of direct-fed microbiota was found to reduce shedding of E. coli O157:H7 in cattle (Peterson et al, 2007;Callaway et al, 2009;Rahal et al, 2015;Wisener et al, 2015;Giordano et al, 2019). The success seems to depend on the probiotic strain(s), immunomodulation of the host, and their metabolism and ability to modify the local milieu, e.g., by the production of short chain acids, such as lactate, butyrate, and acetate (Ogawa et al, 2001;Takahashi et al, 2004;Carey et al, 2008;Fukuda et al, 2011), or/and occupy similar niches in the intestinal tract in which they compete for adhesion to the gut epithelium and nutrients.…”
Section: Alternative Approaches Using Antimicrobial Agents Probioticsmentioning
confidence: 99%
“…STEC gastroenteritis has not been traditionally treated with probiotics/FMT as has been seen with acute gastroenteritis and RCDI. There has been a plethora of evidence suggesting the role of probiotic strains in having an antimicrobial effect on STEC but the effects were dependent on the strain(s) used as reviewed in [126]. Additionally, recombinant receptor mimics have been targeted against STEC [98].…”
Section: Probiotics And/or Prebiotics As Therapeutics To Combat Gastrmentioning
confidence: 99%
“…In the three studies that mimicked human digestive conditions, S. cerevisiae CNCM I-3856 was implicated in having antagonistic effects on STEC including downregulating Stx expression and how the resident microbiota regulates infectivity [126][127][128][129].…”
Section: Probiotics And/or Prebiotics As Therapeutics To Combat Gastrmentioning
confidence: 99%